Husband's Support and Virtuous Wifehood: Literary Analysis of Al Bantani's Thoughts on Women's Legal Protection in Indonesia - Susanto, Aldi; Kisworo, Budi; Bin Ridwan, Rifanto; Yanto, Murni (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Women are guaranteed by the Islamic religion and the law that they will be supported by their husbands. and also women have the obligation to be pious wives so that the purpose of a marriage can be realized. Therefore it is important to study the thoughts of Sheikh Muhammad Nawawi Al-Bantani in the book Uqudulujain Fi Bayani Huquq Az-Zaujain, especially regarding the obligation of a husband to provide a living for his wife and how to become a salihah wife (in the perspective of legal protection for women in Indonesia). This study uses a type of library research with data collection techniques in the form of literature studies using book review techniques. This study concluded that there are 3 obligations of a husband in providing a living to his wife, namely: outward obligations, spiritual obligations, and aqliyah obligations. Whereas the ways to be a salihah wife are: The wife carries out Fardu Ain in Islam, the wife must obey her husband, the wife must leave requests to her husband with something that exceeds her needs, the wife must be patient, the wife must cover her private parts, guarding her tongue from words that can hurt the heart Husband, Protects His Oral From Lying to His Husband, Protects His Oral From Bringing Up Her Husband's Gifts, Puts a Smiling Face When Meeting Husband, Serves Husband Well, Asks Permission When Going From Home To Her Husband, Expands Husband's Heart When Husband Is In Trouble, Takes Care Husband's Treasure and Taking Care of Himself (Having an affair). Whereas in the perspective of legal protection for women in Indonesia, referring to article 31 of the Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage, it can be understood that husband and wife have an equal position, but the wife has the obligation to regulate household affairs, for example in matters of cooking because the husband has carried out his duties. to make a living.